2021
DOI: 10.3390/f12121736
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Classification Based on Sentinel-2 Imagery and Random Forest Classifier in the Eastern Regions of the Qilian Mountains

Abstract: Obtaining accurate forest coverage of tree species is an important basis for the rational use and protection of existing forest resources. However, most current studies have mainly focused on broad tree classification, such as coniferous vs. broadleaf tree species, and a refined tree classification with tree species information is urgently needed. Although airborne LiDAR data or unmanned aerial vehicle (UAV) images can be used to acquire tree information even at the single tree level, this method will encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The results showed that topographic variables played a significant role in tree species classification, and the introduction of topographic variables increased the classification accuracy from 75.60% to 81.70%. Ma et al [10] classified forest tree species in the eastern part of the Qilian Mountains based on Sentinel-2 spectral features, texture features, and topographic features. The results showed that the combination of elevation, slope, slope aspect, and texture features can increase the separation of tree species, with an overall accuracy of 86.49% and a kappa coefficient of 0.83.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that topographic variables played a significant role in tree species classification, and the introduction of topographic variables increased the classification accuracy from 75.60% to 81.70%. Ma et al [10] classified forest tree species in the eastern part of the Qilian Mountains based on Sentinel-2 spectral features, texture features, and topographic features. The results showed that the combination of elevation, slope, slope aspect, and texture features can increase the separation of tree species, with an overall accuracy of 86.49% and a kappa coefficient of 0.83.…”
Section: Introductionmentioning
confidence: 99%
“…In the Grand-Est, the determination of species was rst determined by photointerpretation as spruce or r or as mixed conifers (performed by IGN) and then re ned using Sentinel-2 (S2) spectral time series. Phenology courses are highly suitable for forest tree species discrimination (Grabska et al, 2019;Lisein et al, 2015;Ma et al, 2021). In order to identify and remove every non-spruce pixel, all S2 spectral bands of 10 and 20 m were rst summarized for each of the four quarters of the year, by averaging all cloud-free observations occurring during the quarter.…”
Section: Focus On Spruce Standsmentioning
confidence: 99%
“…Various plant classification techniques are currently available; thus, selecting the most appropriate method depends on the site-specific characteristics. Traditional spatial-based classification techniques such as Random Forest (RF) [11,12] and Support Vector Machine (SVM) [13] have been broadly exploited in numerous studies where comparisons with other classifications have been conducted [14][15][16]. However, recent advancements in machine learning (ML) have led to the development of deep learning classification techniques for plant species classification, such as Convolutional Neural Networks (CNN) [17,18], Long Short-Term Memory Networks (LSTMs) [19,20], Recurrent Neural Networks (RNNs) [21,22] and Multilayer Perceptrons (MLPs) [23].…”
Section: Introductionmentioning
confidence: 99%